ANALISIS LAGRANGIAN NULL NONSTANDAR DAN FUNGSI GAUGE UNTUK HUKUM INERSIA NEWTON : SEBUAH REVIEW - Amelia A.P Ambot; Herry F. Lalus; Hartoyo Yudhawardana (JOURNAL ONLINE OF PHYSICS, 2023)
This paper describes a review of a journal entitled 'Nonstandard Null Lagrangians and Gauge Functions for Newtonian Law of Inertia' which discusses Nonstandard Lagrangian Null solutions for Newton's Law of Inertia. The purpose of this study is to present in detail the Lagrangian Formalism method for generating Nonstandard Lagrangian Null and its Gauge function for Newton's Law of Inertia, as well as the role of action invariant in generating Lagrangian Null and Exact Gauge functions, by deriving a one-dimensional oscillator arm using the basic Lagrangian equations. The Nonstandard Null Lagrangian is derived from the Nonstandard Lagrangian, then the two Lagrangian Null are entered into the action invariant to make it Exact, after the Nonstandard Lagrangian Null is declared Exact, it is substituted into  which represents Newton's Law of Inertia. The results of this research show that an Exact Nonstandard Lagrangian Null can be generated by making the Gauge Function Invariant, so that the first Nonstandard Lagrangian Null and Gauge Function for Newton's Law of Inertia are obtained.